Form of Hate Speech Comments on Najwa Shihab Youtube Channels in The General Election Campaign of President and Vice President of The Republic of Indonesia 2019 - Yuliyanti, Tsalisa; Subyantoro, Subyantoro; Pristiwati, Rahayu (Universitas Negeri Semarang, 2020)
Emerging and spreading hate speech online was a growing phenomenon in social media on youtube. Najwa Shihab was a youtube channel that contains shows and comments on political issues in Indonesia, one of them was the 2019 presidential election campaign. The form of hate speech in comments in the Najwa Shihab Channels was forming grammatical construction and construction of the meaning of one hate speech with other utterances. The purpose of this study was to analyze the illocutionary speech acts on hate speech and to analyze hate speech based on the rule of law in Indonesia. The analysis resulted in hate speech on the Najwa Shihab youtube channel audience comments in the General Election campaign in the discourse of the President and Vice President of the Republic of Indonesia in 2019. The approach that used in this study was a theoretical approach, namely a forensic linguistic approach by utilizing pragmatics for data analysis, and a methodological approach, namely a qualitative descriptive approach. The data on hate speech that was analyzed was a fragment of the audience's comments on two programs, namely Mata Najwa and Catatan Najwa. The results showed that there were nine forms of hate speech. Two forms of hate speech were considered to be the style of speech that was widely used by the public in delivering comments on social media. The forms of the speech were